Modeling Soil Carbon Under Diverse Cropping Systems and Farming Management in Contrasting Climatic Regions in Europe - Begum, Khadiza; Zornoza, Raul; Farina, Roberta; Lemola, Riitta; Álvaro-Fuentes, Jorge; Cerasuolo, Marianna (Frontiers in Environmental Science, 2022)
Sustainable agriculture has been identified as key to achieving the 2030 Agenda for the Sustainable Development Goals, which aims to end poverty and hunger and address climate change while maintaining natural resources. Soil organic carbon (SOC) sequestration is a key soil function for ecosystem services, and storing carbon (C) in soil by changing traditional management practices can represent an important step toward the development of more sustainable agricultural systems in Europe. Within the European project Diverfarming, the process-based ecosystem model ECOSSE was modified and evaluated in four long-term experiments (>8 years) to assess the impact of crop diversification and agricultural management in SOC dynamics. ECOSSE was able to simulate SOC under dry conditions in Mediterranean regions in Spain and Italy. In the site of Murcia, Spain, the addition of manure and cover crop in the diversified systems produced an increase of SOC in 9 years, when compared with the conventional management (16% measured increase, 32% simulated increase). The effect of tillage management on SOC stock in dry soil, in Foggia, Italy and Huesca, Spain, was also modeled, and a positive impact on SOC was predicted when no tillage was practiced. Finally, ECOSSE was used to understand the impact of diversifications in Boreal regions, Finland, where different proportions of legumes and grass were considered in a 4-year crop rotation compared with conventional cereal rotations. Experiments and modeling showed that the loss of SOC in conventional cereal was compensated when grass was introduced in the rotations. A good agreement (NRMSE <10%) and a nonsignificant bias were observed between model and experimental data for all sites. Mitigation scenarios considered in the modeling analysis for the test site Huesca showed that an integrated management of no tillage and manure is the best strategy to increase SOC, ∼51% over 20 years, compared with the baseline scenario (current farmers practice). This study demonstrated the ability of the modified version of ECOSSE to simulate SOC dynamics in diversified cropping systems, with various soil management practices and different climatic conditions.